PENGARUH CAMPURAN PUPUK KANDANG DAN SEKAM PADI TERHADAP HASIL CABAI RAWIT (Capsicum frutecens L) DI TANAH VERTISOL - Wartapa, Agus (Jurnal Ilmu-Ilmu Pertanian, 2016)
The research titled the influence of a mixture of manure and rice husks to the results of chili (Capsicum frutens) aims to determine the additional amount of manure, rice husks combination of manure and rice husks improve result of chili. Research conducted on the area of BP3K Kalibawang of DI Yogyakarta on soil vertosol, began in Marsh 2014 though December 2014. Research used randomized block design arranged in factorial consisted of two treatment with three replications. The first factor manure (P) consists of 5 levels. The second factor rice husk with 5 levels. The parameters of observation:1. The number of branch 6 weeks old; 2. When the appearance of the first lowers; 3. The weight of fruit per plant. The results showed no interaction between the two treatments. Conclusions of this study are: 1. The addition of manure 100% or 4 part give the most of the number and weight of fruit per plant (planting medium soil: manure=1:1) 2. The addition of rice husks 50% or 2 part, give the most of the weight of fruit per plant (planting medium soil rice husks: manure=2:1). 3. There is no interaction of treatment to the number and weight of chilies per plant.